Análise técnico-econômica do cultivo do arroz no perímetro irrigado Morada Nova, Ceará. - Colares, Daniel Santana (2004)
The main objective of this study was to determine the water use efficiency, the economic efficiency and the profit indexes for rice (Oryza sativa, L.) in the Morada Nova Irrigation District, state of Ceará, Brazil, from July to December, 2003. EPAGRI 109 cultivar was cropped in three different soil units: sandyloam, silt and clay loam, the last two called units I and II, respectively. Parshall flumes and siphon tubes were used to measure and apply water to the field basins. The irrigation system used was basin irrigation (inundation). Data used for the economical analysis were obtained from costs and revenues surveyed in each plot evaluated. Irrigation period for planning for the soil and climate conditions of Morada Nova was 120 days. The water use efficiency for sandy soils presented average values of 0.2 kg.m-3; in the case of heavy soils such value was 0.43 kg.m-3. The water application efficiency for clay-loam soils was 66% in average, whereas for sandy-loam was 35%, considering, in both cases, irrigation without deficit. Net profit for a thousand cubic meter, using diverted and applied water methodology, showed superiority for clay-loam soils with values between R$179,00 and R$94,00, while for sandy soils the values were less than R$58,00. Profit analysis for sandy-loam and clay-loam showed feasibility for both soil units, based on conventional criteria of investment analysis, but considering in the simulation a minimum wage of R$240,00/worker, crop plan for the sandy-loam unit was not feasible, according to the obtained results: cost-benefit relation (B/C) equal to 0.98; net present value (VPL) of – 603.9 and “internal rate of return” (TIR) equal to 3.5%. For the case of clay-loam soil the indexes presented feasibility: B/C = 1.145; VPL = R$4.204,10 and TIR = 60.33%.